An analysis of the impact oof age and proximity of death on health care costs in Ireland - Richard Layte (The Economic and Social Research Institute (ESRI), 2007)
Research has shown that older individuals are far more likely to avail of health care and there is concern in a number of countries that the trend toward population ageing may mean that health care expenditures increase to unsustainable levels. However, there is a growing body of evidence that the approach of death rather than age per se may be the main determinant of health care costs. Previous analyses of the relationship between proximity to death and costs have used rare longitudinal data on costs and whether died and none have used a national sample. In this paper we use a more commonly found data type - a national panel survey to show that proximity to death is indeed a more significant predictor of expenditure on GP and hospital services than age. Using random effects panel models we show that there is a significant gradient in costs as death approaches. Controlling for proximity to death there is no age gradient in costs. This conclusion remains unchanged adjusting for differential health inpatient costs across age groups. In fact, adjustment steepens the gradient in costs as death approaches.
Keywords: 330; Ageing; Cost of Dying; Healthcare Expenditure; Panel Survey; Sterblichkeit; Alternde Bevölkerung; Gesundheitskosten; Panel; Schätzung; Irland